Severe Obesity Is Associated With Increased Risk of Early Complications and Extended Length of Stay Following Coronary Artery Bypass Grafting Surgery. Issue 6 (1st June 2016) - Terada, Tasuku; Johnson, Jeffrey A.; Norris, Colleen; Padwal, Raj; Qiu, Weiyu; Sharma, Arya M.; Janzen, Wonita; Forhan, Mary
Abstract : Background: Better understanding of the relationship between obesity and postsurgical adverse outcomes is needed to provide quality and efficient care. We examined the relationship of obesity with the incidence of early adverse outcomes and in‐hospital length of stay following coronary artery bypass grafting surgery. Methods and Results: We analyzed data from 7560 patients who underwent coronary artery bypass grafting. Using body mass index (BMI; in kg/m 2 ) of 18.5 to 24.9 as a reference, the associations of 4 BMI categories (25.0–29.9, 30.0–34.9, 35.0–39.9, and ≥40.0) with rates of operative mortality, overall early complications, subgroups of early complications (ie, infection, renal and pulmonary complications), and length of stay were assessed while adjusting for clinical covariates. There was no difference in operative mortality; however, higher risks of overall complications were observed for patients with BMI 35.0 to 39.9 (adjusted odds ratio 1.35, 95% CI 1.11–1.63) and ≥40.0 (adjusted odds ratio 1.56, 95% CI 1.21–2.01). Subgroup analyses identified obesity as an independent risk factor for infection (BMI 30.0–34.9: adjusted odds ratio 1.60, 95% CI 1.24–2.05; BMI 35.0–39.9: adjusted odds ratio 2.34, 95% CI 1.73–3.17; BMI ≥40.0: adjusted odds ratio 3.29, 95% CI 2.30–4.71). Median length of stay was longer with BMI ≥40.0 than with BMI 18.5 to 24.9 (median 7.0 days [interquartile range 5 to 10] versus 6.0 days [interquartile range 5 to 9], P =0.026). Conclusions: BMI ≥40.0 was an independent risk factor for longer length of stay, and infection was a potentially modifiable risk factor. Greater perioperative attention and intervention to control the risks associated with infection and length of stay in patients with BMI ≥40.0 may improve patient care quality and efficiency.